HUBUNGAN STATUS GIZI IBU HAMIL DENGAN KADAR HB BAYI LAHIR - Heni Purwanti (Jurnal Medika : Karya Ilmiah Kesehatan, 2018)
Maternal anemia affect the fetus, including miscarriage, intrauterine death, prematurity high labor, low birth weight, birth with anemia, congenital defects can occur, your baby gets an infection through perinatal mortality and low intelligence Manuaba (2007). The study aims to determine the The relationship between the nutritional status of pregnant women with hemoglobin levels newborns in UPTD sub-district Puskesmas Tiron Banyakan Kediri, East Java in 2017. This study used cross sectional design by using logistic regression analysis. The results showed the value of OR of 10.3 (95% CI : 1,47-72,3) which means that the mother's nutritional status are less likely 10.3 times more likely to give birth to babies with low hemoglobin levels (anemia) compared to the nutritional status of mothers was good once controlled by the variable maternal age, and maternal Hb. Suggestions for community health centre in the area to Improving the quality of health centers ANC primarily related to maternal nutrition during pregnancy to prevent maternal anemia that can affect newborn anemia.